Synthesis and biological evaluation of 3, 5-disubstituted-4-alkynylisoxozales as a novel class of HSP90 inhibitors. Issue 16 (15th August 2015) - Sun, Jian; Lin, Cai; Qin, Xiaochu; Dong, Xiaoping; Tu, Zhengchao; Tang, Fei; Chen, Chaonan; Zhang, Jiancun
Graphical abstract